16. Trumpet and Orchestra Concert in D Major by Georg Philipp Telemann in Interpretation Vision of Wynton Marsalis and Rafael Méndez - Horez Iulian (Sciendo, 2020)
Like most baroque concerts, the Concerto for trumpet and orchestra in D major by Georg Philipp Telemann raises particular problems of interpretation. It is a concert written in the head register of the trumpet, with frequent references in the acute register. I should mention that the head register of a trumpet depends on its size. At a normal trumpet in and flat (and not piccolo), the acute register is from do (and flat from the first octave) to the next do ascendant. The head register continues from do2 to do3. In the trumpets in do, re, mi flat, fa, sol, the principle remains the same, with a variability depending on the size of the trumpet, except that in the acute record the other notes correspond to that of the flat, but the upper limit is generally the same.